(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This study proposes a new assessment methodology based on an integrated and modular approach, developed through the analysis of the advantages and shortcomings of existing methods for evaluating socio-economic losses in emergency situations. The proposed methodology allows for real-time data processing and adaptation to various types of emergencies.